PESANTREN SALAF: PERUBAHAN SOSIAL DAN SUBLIMASI IDENTITAS DENGAN KOMBINASI TASAWUF, FIQIH DAN TAUHID (Model Pesantren di Kabupaten Tasikmalaya Jawa Barat) - Muhammad Solahudin; Ecep Ismail; Irwan Abdurrohman (Syifa al-Qulub, 2020)
On the one hand, in the environment of the Pesantren salaf community, a kind of environment and tradition is formed which shows its unique, even unique characteristics, which are only understood by the community. Gus Dur, in this case, stated that the Pesantren salaf community is a community that has its own subcultural in the middle of society with the complexity of the problems in it. But on the other hand, there is a very rapid development of science and technology, so it demands pesantren salaf to make changes to adjust to the times, both in terms of the education system, the boarding school environment, institutions, leadership patterns, and others. Therefore, the study contained in the title "Pesantren Salaf: Social Change and Sublimation of Identity (Pesantren Model in West Java)", is very important to be carried out.The purpose of this study is none other than to find the concept of changes that occur in Pesantren salaf in West Java. For more details, they are: 1) uncovering the factors that drive changes in pesantren in West Java; 2) reveal pesantren's efforts in facing the challenges of the times, and 3) find forms of changes that occur in the Pesantren salaf in West Java.This research departs from a thought that social change will occur due to four things. First, Evolution. This theory states that humans as part of a cultured society will naturally develop gradually from simple forms to complex and perfect stages. Second, Conflict. This theory strongly believes that change will only occur if there is conflict. Third. Functional Theory. Social change occurs because of the disharmony between cultural elements. Fourth, Cycle Theory. Social change by itself will occur and cannot be controlled.The method used in this research is descriptive. In the process, the data is collected and compiled. After the data is collected and arranged in such a way, the authors analyze it and provide interpretation, with a qualitative approach. So that it is expected to be able to uncover the realities of the Pesantren salaf which are changing in the community.The results of the study stated that the Pesantren salaf can adapt well to social change by bringing up certain identities. This shift in identity needs to be examined and studied through the theory of action put forward by Max Weber. First, zweckrational. This theory is known as rational-purpose. In doing something always with a good and accurate calculation. Second, wertrational or rational-values. The involvement of the subject is directly involved in matters of absolute importance. The four traditionalists. This theory of action rests on established and established customs or traditions. Traditionalist theories respect existing authority.